2017
DOI: 10.18359/rcin.1911
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la lombriz roja californiana (Eisenia foetida), sobre el crecimiento de microorganismos en suelos contaminados con mercurio de Segovia, Antoquia

Abstract: <p>Dentro de las actividades que alteran la composición del suelo está la minería, que causa el aumento de daños visibles al suelo mediante la creación de minas a cielo abierto, escombreras, estanques de residuos y otras instalaciones de minas. El objetivo principal de este trabajo fue evaluar el efecto de la lombriz roja californiana sobre el crecimiento de microorganismos en suelos contaminados con mercurio en el municipio de Segovia, Antioquia. Estos suelos representan una problemática importante debi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…In addition, earthworms are frequently used in the determination of soil quality, taking into account their ability to accumulate different environmental xenobiotics (Marinussen et al 1997). Earthworms also participate in the bioremediation of contaminated soils (Zapata et al 2016;Barbaran 2017). The effect of these contaminating substances will depend in part on their bioavailability, the degree of biotransformation into substances of lower toxicity and their elimination (Viswanhathan 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, earthworms are frequently used in the determination of soil quality, taking into account their ability to accumulate different environmental xenobiotics (Marinussen et al 1997). Earthworms also participate in the bioremediation of contaminated soils (Zapata et al 2016;Barbaran 2017). The effect of these contaminating substances will depend in part on their bioavailability, the degree of biotransformation into substances of lower toxicity and their elimination (Viswanhathan 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For further studies, we propose to evaluate the biochemical responses of Eisenia fetida to the hydrogel through soil exposure tests, which in addition to allowing us to study the chronic effects derived from exposure and ingestion will provide information on the dynamics of the microbial community [ 71 ], changes in the ability of earthworms to form galleries, and agitation and removal of the pollutant in the soil [ 72 ]. For the characterization of the oxidative stress mechanisms generated in the earthworms due to exposure to the hydrogel, the quantification of a battery of enzymes involved in oxidative stress is contemplated.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that through their mucilaginous secretions and transformation of organic material, worms increase the activity of microorganisms and the availability of nutrients. Likewise, it has been reported that worms can stimulate bacteria, fungi, and other species related to the degradation of some organic pollutants (Zapata et al 2017).…”
Section: Introductionmentioning
confidence: 99%